Developing English Oral Communication Instructional Materials for Nursing School - Agustinus Lekipiouw (Kayon Media, 2018)
Increasing the quality of education can be done in several aspects such as by wise way, management, education equipment’s, and resourceful people for management. Teacher is the key and has an important role in deciding the successful of education in an institution. The descriptive correlation design is used in this study. The study conducted at State SMP in Ambon city which about 22 schools with the population is about 950 people and the sample of the study is about 274 teachers. Random proportional is applied in this study. Questionnaire is distributed to collect the data. The study is aimed to find the significant correlation between implementation of supervising teaching with teachers’ work performance at state SMP in Ambon city. The significant correlation between managerial skill of the headmasters with teachers’ work performance at State SMP in Ambon city.Peningkatan kualitas pendidikan dapat dilakukan dalam beberapa aspek, seperti: kebijakan, manajemen, sarana prasarana, dan sumber daya pengelola pendidikan. Guru sebagai sumber daya kunci pelaksanaan pendidikan memegang peranan penting dan menentukan. Sukses tidaknya pelaksanaan pendidikan ditingkat lembaga terutama tergantung pada guru. Penelitian ini dirancang dengan rancangan penelitian diskriptif korelasional. Dilaksanakan di SMP Negeri di Kota Ambon sejumlah 22 lembaga dengan populasi 950 orang dan jumlah sampel 274 orang. Sampel diambil dengan random proporsional. Penelitian ini menggunakan kuesioner atau angket sebagai instrumen dalam pengumpulan data penelitian. Dari hasil penelitian menunjukkan terdapat hubungan yang signifikan antara pelaksanaan supervisi pengajaran dengan kinerja guru SMP Negeri di Kota Ambon. Terdapat hubungan yang signifikan antara keterampilan manajerial kepala sekolah dengan kinerja guru SMP Negeri di Kota Ambon.